On the Exponential Dichotomy on $\mathbb{R}$ of Linear Differential Equations in $\mathbb{R}^n$ - Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
New results of the investigation of exponential dichotomy on the entire axis of linear differentialequations in $\mathbb{R}^n$ are presented.